TOTAL QUALITY MANAGEMENT IN ISLAMIC EDUCATION INSTITUTION - Indriyenni Indriyenni (Ta'dib, 2017)
There have been five characteristics of a qualified school such as focusing on the customer, total engagement, measurement, commitment, and continuous improvement. Every educational institution including Islamic boarding school (IBS) is required to provide the best services to its customers. In this way, IBS need to be supported by a good management system; the existence of a regular mindset (administrative thinking), the implementation of regular activities (administrative behavior), attitude to the task activities well (administrative attitude), and so forth. To answer the various problems that exist in the educational environment the management should have an Integrated or Total Quality Management (TQM). One of its goals is to transform a school institution into a sincere team, without conflict and internal competition to achieve a single goal of satisfying all customers. TQM will provide educators professional solutions to meet today’s challenges and the future. It is because TQM can be used to build alliance between education, business and government. TQM can also shape the community responsive to the changing demands of society in this era of globalization. Besides, TQM form a responsive school and is able to respond to changes that occur in the field of education in order to give satisfaction to stakeholder.